Composite electrode unit, electrochemical water treatment system and electrochemical water treatment method
By using a composite electrode unit of a porous insulating filler layer and a catalytic electrode in an electrochemical water treatment system, the problems of low hydroxide utilization efficiency and high energy consumption of high tank pressure are solved, and the low energy consumption and high efficiency of electroscaling effect is achieved, which is suitable for industrial circulating water systems.
Patent Information
- Application Number
- CN202510728100.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-03
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2045-06-03
AI Technical Summary
In the existing electrochemical hardening and chlorine removal technology, the low utilization efficiency of hydroxide roots and high electrolytic cell tank pressure lead to high energy consumption, and the electrode self-scaling problem is limited, which limits its application economy in large-scale industrial circulating water systems.
The composite electrode unit composed of a porous insulating filler layer inhibits hydroxide migration through hydrophobic action, combines forced diffusion and catalytic electrode to reduce voltage, and uses alternating current to achieve automatic descaling, reducing the high energy consumption caused by high tank pressure.
It improves the utilization rate of hydroxide, reduces the voltage and energy consumption of electrolyzed water, achieves a low-energy consumption and efficient electroscaling effect, reduces the amount of water replenishment and sewage discharge, and reduces the operation and maintenance costs.
Smart Images

Figure CN120247179A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water treatment, and mainly relates to a composite electrode unit, an electrochemical water treatment system and an electrochemical water treatment method. Background Art
[0002] In industrial water systems, circulating cooling water, as the core medium for maintaining equipment operation, faces severe challenges in water quality management: The traditional process relies on repeated concentration and circulation patterns, which are prone to mineral salt deposition, leading to frequent scaling. Hard scale not only accelerates the electrochemical corrosion of metal pipelines, posing a risk of local perforation, but also significantly reduces the heat transfer efficiency of heat exchange equipment, directly affecting production efficiency. For a long time, the industry has generally adopted chemical intervention methods such as adjusting the pH value with acids and alkalis or adding scale inhibitors. Although it can relieve the scaling problem in the short term, it has disadvantages such as high chemical consumption, potential secondary pollution hazards, and high operation and maintenance costs. At the same time, the concentration of chloride ions (chloride radicals) in water gradually enhances the corrosion of metal equipment. With the deepening of the concept of green manufacturing, new hard and chlorine removal technologies based on electrochemical principles have emerged.
[0003] The electrochemical hard and chlorine removal technology achieves a double breakthrough in water quality regulation and resource recovery through the electrolysis process. Its basic principle is: In the cathode chamber, a large amount of hydroxide ions are generated through the electrolysis reaction, promoting the conversion of bicarbonate in the water body into carbonate in an alkaline environment, driving the directional migration of scale-forming ions such as calcium ions and magnesium ions and preferentially forming crystalline precipitates such as calcium carbonate and magnesium hydroxide to achieve targeted separation of hard scale; in the anode chamber, HClO / ClO - and trace amounts of chlorine gas are generated by the oxidation of chloride ions. At the same time, the hydrogen ions generated by the electrolysis of water can dynamically adjust the pH value of the system to form an adaptive scale inhibition environment. This technology not only abandons the external addition of traditional scale inhibitors and acid-base agents, avoiding the risk of chemical residue pollution from the source, but also inhibits the growth of microorganisms through the simultaneously generated active chlorine substances, breaking the industry problem of the mutual reinforcement of scaling and corrosion. After treatment, the concentration multiple of the circulating water system is significantly increased, while reducing the makeup water volume and sewage discharge volume, achieving the coordinated optimization of water resource utilization efficiency and environmental benefits, providing a technical path with both cleanliness and economy for industrial circulating water management.
[0004] The above technical route has several serious problems: First, the utilization efficiency of hydroxide ions generated by electrolyzing water is low; Second, the single-stage voltage of the electrolysis unit is high; Third, there is a problem of self-scaling of the electrodes. For example, the Chinese patent "CN101585569A - Circulating water electrolysis descaling device and descaling method" discloses a circulating water electrolysis descaling device and method, belonging to the field of water treatment environmental protection technology. The core of the device includes a metal reaction chamber (serving as the electrolysis cathode), an anode, a test electrode, an ultrasonic cleaner, and an automatic control system. Its working principle is divided into two stages: electrolysis scaling and cleaning descaling. During the electrolysis process, hydroxide ions are generated in the cathode chamber, causing calcium ions, magnesium ions, and carbonate ions in the water to combine to form loose soft scale, which deposits on the inner wall of the reaction chamber. At the same time, the anode oxidizes chloride ions to generate bactericidal substances such as hypochlorous acid and chlorine gas. When the test electrode detects that the scale layer thickens and the resistance exceeds the limit, the system automatically switches to the cleaning mode, closes the inlet and outlet valves, and starts the ultrasonic cleaner to peel off the scale, which is discharged through the sewage valve. This technology combines electrolysis and ultrasonic physical cleaning, without the need for chemical scale inhibitors, and realizes the integration of scale removal, sterilization, and water quality softening by dynamically adjusting the pH and active substances. The concentration multiple of the circulating water is significantly increased (the calcium hardness reduction reaches 44%), and it has an automatic control and an epoxy resin anti-corrosion structure, effectively solving the problems of strong dependence on chemicals, frequent maintenance, and secondary pollution in traditional methods.
[0005] However, the applicant found during the implementation of the present invention that the electrolysis system in the Chinese patent "CN101585569A - Circulating water electrolysis descaling device and descaling method" adopts an integrated tank design. During the electrolysis descaling process, the anode and cathode are in the same reaction chamber and there is no ion isolation, resulting in a dynamically neutral environment for the overall system, and the utilization efficiency of the hydroxide ions generated by electrolysis is low. At the same time, the distance between the anode and cathode is relatively large, and the high electrolysis unit cell voltage leads to increased power consumption. Experimental data shows that at the same current density, for every 1 cm increase in the distance between the two electrodes, the cell voltage rises by about 0.5 - 1.2 V, and the energy consumption increase can reach 15% - 30%. This high energy consumption characteristic limits the application economy of this technology in large-scale industrial circulating water systems.
[0006] In order to solve the above problems, the present invention is proposed. Summary of the Invention
[0007] This application provides a composite electrode unit, an electrochemical water treatment system, and an electrochemical water treatment method. Compared with the prior art, the breakthroughs of this application include: (1) A porous insulating filler layer is used, combined with the cathode and anode, to form an integrated composite electrode unit; the porous characteristics of the porous insulating filler layer enable water molecules to pass through in a constrained manner; (2) An internal electric field is formed within the porous insulating filler layer to resist the applied voltage, reducing the high energy consumption caused by a high cell voltage; (3) Due to the hydrophobic effect of the porous insulating filler layer, the migration of hydroxide ions generated at the cathode is inhibited, and then forced diffusion is carried out through a high flow rate to the main body of the aqueous phase in the cathode chamber, accelerating its combination with scale-forming ions such as calcium and magnesium ions, and improving the utilization rate of hydroxide ions; (4) Due to the hydrophobic effect of the porous insulating filler layer, the migration of H + is inhibited, and then forced diffusion is carried out through a high flow rate, enabling an acidic environment to be formed in the anode region, promoting the oxidation of chloride ions into bactericidal substances such as hypochlorous acid and chlorine in the acidic environment; (5) A catalytic electrode for electrolyzing water is used to further reduce the voltage of electrolyzing water and reduce energy consumption; (6) In addition to directly using direct current, alternating current (such as square wave alternating current) is used to automatically switch the cathode and anode, realizing automatic descaling. Through the above technical inventions, this application improves the defects of the existing electric descaling technology, greatly improves the electric descaling efficiency, and reduces the power consumption.
[0008] In the first aspect of this application, a composite electrode unit is provided, which includes: an electrolyzed water cathode, a porous insulating filler layer, and an electrolyzed water anode; the porous insulating filler layer is located between the electrolyzed water cathode and the electrolyzed water anode; The internal material of the porous insulating filler layer itself does not contain exchangeable ions, and this internal part refers to the non-surface part.
[0009] Preferably, the electrolyzed water cathode, the porous insulating filler layer, and the electrolyzed water anode are mutually adhered.
[0010] One of the key points of this invention lies in that the internal material of the porous insulating filler layer itself does not contain exchangeable ions. In this invention, according to the way ions in the aqueous solution pass through the porous filler layer when the porous filler layer is placed in the aqueous solution containing ions, a distinction is made between whether the filler layer material itself is "insulating" or "conductive". If the porous filler layer material itself has exchangeable ions, for example, the anion exchange resin material itself has anions available for ion exchange, and the cation exchange resin material itself has cations available for ion exchange, then the ions in the aqueous solution can migrate through the porous filler layer in two ways: A. Migrate through ion exchange with the ions of the porous filler layer material itself, and this migration is selective. For example, the anion exchange resin only allows anions to migrate and does not allow cations to migrate, and the cation exchange resin only allows cations to migrate and does not allow anions to migrate; B. Migration occurs through the flow of the aqueous solution itself within the pores of the porous material. This migration is non-selective, and both anions and cations in the aqueous solution can migrate.
[0011] Therefore, when the porous filler layer material itself has exchangeable ions, since ion migration mode A occurs through the porous filler layer material itself, it appears that the porous filler layer itself is a conductive ion conductor, i.e., conductive. Thus, a porous filler layer whose material itself has exchangeable ions is called a "porous conductive filler layer".
[0012] If the porous filler layer material itself does not contain exchangeable ions, i.e., the material itself does not provide an ion exchange function, when this porous filler layer is placed in an aqueous solution containing ions, the above ion migration mode A does not exist, and ion migration only relies on the above ion migration mode B. Then it appears that the porous filler layer itself is non-conductive and only conducts electricity through the flow of the aqueous solution in the pores. Thus, a porous filler layer whose material itself does not contain exchangeable ions is called a "porous insulating filler layer", which is exactly the filler layer used in this application.
[0013] The above composite electrode unit is the smallest technical unit of this application and also the smallest salable patent implementation unit. The above composite electrode unit can be placed in an electrolytic cell and start working after applying a voltage.
[0014] The internal material of the porous insulating filler layer itself does not contain exchangeable ions, and the internal refers to the non-surface part. In other words, the internal material of the porous insulating filler layer itself does not contain exchangeable ions, and ion transfer cannot occur through ion exchange in the internal material of the porous insulating filler layer. Then the ions in the external solution of the porous insulating filler layer cannot pass through the porous insulating filler layer only through the ion exchange of the porous insulating filler layer material itself.
[0015] Of course, the surface of the porous insulating filler layer may or may not contain ions, which does not affect the fact that the ions in the external solution of the porous insulating filler layer cannot pass through the porous insulating filler layer only through ion exchange with the porous insulating filler layer material itself.
[0016] In the present invention, there is no requirement for whether the porous insulating filler layer material is hydrophobic or hydrophilic. Preferably, however, the entire porous insulating filler layer is a hydrophobic material. Because a hydrophobic material can inhibit the flow of the aqueous solution within the pores of the porous insulating filler layer, i.e., inhibit the migration rate of the aforementioned ion migration mode B.
[0017] Or the internal material of the porous insulating filler layer itself is a hydrophobic material, and the surface is a hydrophilic material, where the internal refers to the non-surface part. This setting can also inhibit the migration rate of the aforementioned ion migration mode B.
[0018] Of course, if the porous insulating filler layer is made of a hydrophilic material, the solution of the present application can also be partially realized. However, since the ion migration mode B is accelerated, more hydroxide ions in the cathode chamber fail to combine with calcium ions or magnesium ions to form precipitates and migrate to the anode chamber through the ion migration mode B, resulting in a lower utilization efficiency of hydroxide ions than that of the porous insulating filler layer made of a hydrophobic material. However, a low efficiency does not mean it is not feasible.
[0019] Preferably, the porosity of the porous insulating filler layer is 1% - 98%, the thickness is 0.05 - 5 mm, and the pore diameter is 0.1 - 500 μm.
[0020] More preferably, the porosity is 50% - 98%. Even more preferably, the porosity is 52% - 98%. Even more preferably, the porosity is 55% - 98%. Further even more preferably, the porosity is 60% - 98%. Furthermore, the porosity range can be 60% - 75%, 60% - 73%, 52% - 75%, 52% - 73%, 52% - 68%, 55% - 75%, 55% - 73%, or 55% - 68%, etc.
[0021] More preferably, the thickness range can be 0.05 - 5 mm, 0.1 - 5 mm, 0.18 - 5 mm, 0.2 - 5 mm, 0.5 - 5 mm, 1 - 5 mm, 1.2 - 5 mm, 1.5 - 5 mm, 2 - 5 mm, 2.2 - 5 mm, 2.5 - 5 mm, 0.2 - 2.5 mm, or 0.2 - 2.2 mm, etc.
[0022] The pore diameter range can be 0.1 - 0.5 μm, 0.2 - 0.8 μm, 0.3 - 500 μm, 0.5 - 500 μm, 0.1 - 0.3 μm, 0.3 - 1 μm, 0.1 - 0.4 μm, 1 - 500 μm, 0.2 - 0.6 μm, 10 - 200 μm, 0.2 - 0.6 μm, or 10 - 500 μm, etc.
[0023] Preferably, the material of the porous insulating filler layer is selected from: polyethylene, polystyrene, polyphenylene sulfide, polyvinyl chloride, polypropylene, polyurethane, polyamide, polyethersulfone, polypropylene hollow fiber, polytetrafluoroethylene, polyvinylidene fluoride, sulfonated polyether ether ketone, polybenzimidazole, polyimide, asbestos, alumina, silicon carbide, silicon nitride, zirconia, boron nitride, mullite, cordierite, aluminum titanate, silica, or a combination of one or more of them.
[0024] That is, the material of the porous insulating filler layer can be a single material, a mixed material of multiple materials, or a composite material composed of multiple single material layers.
[0025] In other words, the porous insulating filler layer is selected from: a polyethylene layer, a polystyrene layer, a polyphenylene sulfide layer, a polyvinyl chloride layer, a polypropylene layer, a polyurethane layer, a polyamide layer, a polyethersulfone layer, a polypropylene hollow fiber layer, a polytetrafluoroethylene composite layer, a polyvinylidene fluoride layer, a sulfonated polyether ether ketone layer, a polybenzimidazole layer, a polyimide layer, an asbestos layer, an alumina layer, a silicon carbide layer, a silicon nitride layer, a zirconia layer, a boron nitride layer, a mullite layer, a cordierite layer, a titania aluminate layer, a silica layer, or a combination of one or more thereof.
[0026] In addition, the porous insulating filler layer may also be selected as: an organic layer doped with inorganic substances such as iron oxides.
[0027] Preferably, the surface of the porous insulating filler layer is modified. In other words, the surface of the porous insulating filler layer has a modified layer. The modified layer may be a hydrophilic layer. The hydrophilic modification of the surface of the porous insulating filler layer does not affect that the interior of the porous insulating filler layer remains a hydrophobic material, so the passage of water is still restricted.
[0028] In addition, the graft modification of the surface of the porous insulating filler layer also does not affect the nature of the interior material (i.e., the bulk phase) of the porous insulating filler layer itself without cations and anions, and the interior (i.e., the bulk phase) of the porous insulating filler layer still does not contain ions.
[0029] In this application, due to the hydrophobic material of the porous insulating filler layer, the passing rates of water and ions through its pores are extremely slow. Therefore, the above ion migration mode B also proceeds extremely slowly. Therefore, the hydroxide ions generated by the electrolysis of water in the cathode chamber are almost consumed by the calcium and magnesium ions in the cathode chamber before passing through the porous insulating filler layer and entering the anode chamber.
[0030] Of course, whether or not a voltage is applied between the anode and the cathode, protons and hydroxide ions can slowly pass through the porous insulating filler layer and mix (the passing rates of protons and hydroxide ions when a voltage is applied are greater than those when no voltage is applied). However, protons and hydroxide ions are discharged from the anode chamber and the cathode chamber respectively before they mix, so acidic water and alkaline water can be obtained respectively.
[0031] The second aspect of this application provides an electrochemical water treatment system, which includes: a reaction chamber; The reaction chamber is provided with: the composite electrode unit described in the first aspect; In the reaction chamber, the chamber on the cathode side of the electrolyzed water of the composite electrode unit is the cathode chamber, and the chamber on the anode side of the electrolyzed water of the composite electrode unit is the anode chamber.
[0032] Preferably, the reaction chamber further includes: a power source for providing direct current or alternating current to the electrolyzed water cathode and the electrolyzed water anode.
[0033] Preferably, the top plate of the reaction chamber is attached to the top of the composite electrode unit, and the bottom plate of the reaction chamber is attached to the bottom of the composite electrode unit to physically separate the cathode chamber and the anode chamber by the composite electrode unit, preventing direct mixing of the water on both sides.
[0034] Preferably, the system further includes: a raw water tank and a recycled water tank; The raw water tank is communicated with the anode chamber through an anode chamber inlet pipeline; The raw water tank is communicated with the cathode chamber through a cathode chamber inlet pipeline; The recycled water tank is communicated with the anode chamber through an anode chamber outlet pipeline; The recycled water tank is communicated with the cathode chamber through a cathode chamber outlet pipeline.
[0035] Preferably, the system further includes a filtering device arranged on the cathode chamber outlet pipeline for filtering solid substances in the liquid of the cathode chamber outlet pipeline.
[0036] Preferably, the raw water tank and the recycled water tank are communicated through a circulation pipeline. In this way, the recycled water in the recycled water tank can enter the reaction chamber again through the raw water tank for electrochemical treatment. The whole process can be cycled multiple times until the effluent quality of the recycled water meets the standard.
[0037] Preferably, the cathode of the electrolyzed water in this application is a mesh electrode, and its material is any catalyst that can catalyze the cathode reaction of electrolyzed water. The anode of the electrolyzed water in this application is a mesh electrode, and its material is a catalyst that can catalyze the anode reaction of electrolyzed water under acidic conditions.
[0038] In the third aspect of this application, an electrochemical water treatment method is provided. The method is carried out using the electrochemical water treatment system according to any item of the second aspect, and the method includes the following steps: Inject the raw water containing calcium ions and / or magnesium ions into the cathode chamber and the anode chamber respectively, turn on the power supply, apply direct current or alternating current between the electrolyzed water cathode and the electrolyzed water anode, and perform electrolysis to carry out an electrolyzed water reaction in the composite electrode unit; When direct current is provided: hydrogen is generated in the cathode chamber during electrolyzed water while an alkaline environment is formed, so that calcium ions and / or magnesium ions form solid substances and precipitate to reduce the hardness of the water; oxygen is generated in the anode chamber during electrolyzed water while an acidic environment is formed; finally, alkaline water containing solid substances is obtained in the cathode chamber, and acidic water is obtained in the anode chamber; When alternating current is provided: Before the current direction changes within each alternating current cycle: When electrolyzing water, hydrogen is generated in the cathode chamber while an alkaline environment is formed, causing calcium ions and / or magnesium ions to form solid precipitates, and some of the solid precipitates crystallize on the surface of the original electrolyzed water cathode; when electrolyzing water, oxygen is generated in the anode chamber while an acidic environment is formed. After the current direction changes within each alternating current cycle: The electrolyzed water cathode and the electrolyzed water anode are inverted, causing the original electrolyzed water anode to become a temporary cathode and start generating hydroxide ions, and the original electrolyzed water cathode to become a temporary anode and start generating hydrogen ions. The hydrogen ions dissolve the solid substances crystallized on the surface of the original electrolyzed water cathode, achieving in-situ self-cleaning of the electrolyzed water cathode. In the next alternating current cycle, in the cathode chamber, calcium ions and / or magnesium ions in the water continuously precipitate out, achieving the purpose of reducing the water hardness. Finally, alkaline water containing solid substances is obtained in the cathode chamber, and acidic water is obtained in the anode chamber.
[0039] Preferably, when the raw water also contains chloride ions, the chloride ions in the anode chamber are oxidized to chlorine gas and removed. The acidic water obtained in the anode chamber is acidic water containing dissolved chlorine and has a self-bacteriostatic effect.
[0040] Preferably, when the method is carried out using the above-mentioned electrochemical water treatment system: The raw water tank contains raw water containing calcium ions and / or magnesium ions. The obtained alkaline water and acidic water containing solid substances are discharged into the reclaimed water tank through the cathode chamber outlet pipeline and the anode chamber outlet pipeline respectively and mixed to obtain neutral water.
[0041] Preferably, the solid substances in the alkaline water containing solid substances are filtered by the filtering device. Of course, the filtering device may not be provided, and the solid substances can be removed by means of solid-liquid separation such as precipitation and pressure filtration of the water in the reclaimed water tank.
[0042] Preferably, the chlorine gas in the acidic water containing chlorine can be discharged into the reclaimed water tank after aeration. For example, an acid water tank is provided on the anode chamber outlet pipeline for aeration. The chlorine gas discharge pipeline of the acid water tank is connected to an absorption tower. Sodium hydroxide solution is sprayed in the absorption tower, and sodium hypochlorite, a valuable chemical product, is formed by the reaction of sodium hydroxide and chlorine gas.
[0043] Preferably, the voltage of the direct current or alternating current is: 1.5V - 30V.
[0044] Preferably, when applying the direct current or alternating current, the current density on the electrolyzed water cathode or the electrolyzed water anode is 1 - 1000 A / m 2。
[0045] In addition, the electrochemical water treatment system of the present application is essentially an electroscale removal device, which is essentially different from the conventional electrolytic water device: 1. First, in terms of the objective: The conventional electrolytic water device "realizes the electrochemical reaction through the migration of hydroxide ions or hydrogen ions", and its main products are hydrogen and oxygen. Its hydroxide ions or hydrogen ions need to quickly pass through the membrane to reach the anode or cathode. For example, in CN116334647A, the electrolytic water device "realizes the electrochemical reaction through the migration of hydroxide ions", and its main products are hydrogen and oxygen. Its hydroxide ions need to quickly pass through the membrane to reach the anode to participate in the electrolytic reaction to produce oxygen.
[0046] The characteristic of the composite electrode unit in the electrochemical water treatment system of the present application is that the porous insulating filler layer should "block the migration of hydroxide ions" so that the hydroxide ions are retained as much as possible in the cathode chamber to combine with calcium and magnesium ions.
[0047] 2. In terms of the device structure: The characteristics of the conventional electrolytic water device (such as CN116334647A) are as follows: In the conventional electrolytic water device, there is a certain distance between the cathode, anode, and membrane, and the three are not in contact. The cathode and anode are located on both sides of the electrolytic cell, and the membrane is located in the middle of the electrolytic cell. The cathode chamber for accommodating the electrolyte is between the cathode and the membrane. The anode chamber for accommodating the electrolyte is between the anode and the membrane. Therefore, when a voltage is applied between the cathode and the anode, the electrolytes in the entire cathode chamber and the entire anode chamber between the cathode and the anode are in the current loop and participate in the electrolytic water reaction.
[0048] At the same time, hydrogen ions or hydroxide ions pass through the membrane to participate in the electrolytic water reaction. The electrolytes in the entire cathode chamber and the entire anode chamber undergo electrolytic water reactions to produce hydrogen and oxygen.
[0049] The main purpose of the electrochemical water treatment system of the present application is not to produce hydrogen and oxygen but to remove scale electrochemically, and its characteristics are as follows: The electrolytic water cathode, the electrolytic water anode, and the porous insulating filler layer are mutually adhered to form a gapless composite electrode unit. This gapless composite electrode unit is located in the middle of the reaction chamber. Between the electrolytic water cathode of the gapless composite electrode and the side wall of the reaction chamber is a cathode chamber for accommodating raw water containing calcium ions and / or magnesium ions. Between the electrolytic water anode of the gapless composite electrode and the other side wall of the reaction chamber is an anode chamber for accommodating raw water containing calcium ions and / or magnesium ions. Therefore, when a voltage is applied between the electrolytic water cathode and the electrolytic water anode, only the raw water in the gapless composite electrode unit is in the current loop and participates in the electrolytic water reaction. The raw water in the cathode chamber and the anode chamber outside the gapless composite electrode unit is not in the current loop and does not participate in the electrolytic water reaction, but only receives the electrolytic products transferred from the gapless composite electrode unit through forced diffusion to carry out conventional chemical reactions (for example, the water in the cathode chamber receives the hydroxide ions generated on the cathode surface to generate calcium and magnesium precipitates, and the water in the anode chamber receives H + +
[0050] and Cl2 or hypochlorous acid, etc. for chemical disinfection, etc.).
[0051] Therefore, only that part of the raw water located in the gapless composite electrode unit (the volume ratio to the raw water in the cathode chamber and the anode chamber outside the entire gapless composite electrode unit may be one percent or one-thousandth) participates in the electrolytic water reaction.
[0052] The electrolytic water generates hydroxide ions at the cathode, and then through high flow rate, it is forced to diffuse into the main body of the water phase in the cathode chamber, accelerating its combination with scale-forming ions such as calcium and magnesium ions, and rapidly crystallizing and precipitating, improving the utilization rate of hydroxide ions. + H
[0053] 3. The differences between the membrane of a conventional electrolytic water device and the porous insulating filler layer of the electrolytic scale removal device of the present application are as follows: The requirements for the membrane of a conventional electrolytic water device are: low resistivity, high conductivity, and the ability to enable anions and / or cations in the electrolyte to quickly pass through the membrane to participate in the electrolytic reaction. Generally, the membrane material of a conventional electrolytic water device itself contains exchangeable ions to undergo ion exchange with the electrolyte so that anions and / or cations in the electrolyte can quickly pass through the membrane to participate in the electrolytic reaction.
[0054] The purpose of the porous insulating filler layer of the present application is to strongly inhibit water and ions from passing through the porous insulating filler layer, so as to prevent the hydroxide ions generated at the cathode from passing through the porous insulating filler layer to combine with the hydrogen ions at the anode, and also prevent the hydrogen ions generated at the anode from passing through the porous insulating filler layer to combine with the hydroxide ions generated at the cathode. Because both of these will reduce the utilization rate of hydroxide scale removal.
[0055] Therefore, the material of the porous insulating filler layer of the present application itself does not contain exchangeable ions, so as to prevent hydroxide ions and hydrogen ions in water from passing through the porous insulating filler layer through ion exchange (i.e., ion migration mode A proposed on page 3 of the specification of the present application).
[0056] In addition, the porous insulating filler layer of the present application has porous characteristics and is relatively thick (preferably 1-5 mm), and is preferably a hydrophobic material, etc. These can all slow down the passage of water and ions through the porous insulating filler layer, that is, inhibit the migration rate of ion migration mode B proposed on page 3 of the specification of the present application.
[0057] 4. In terms of the usage method: The current of the electrolyzed water device is preferably as large as possible to accelerate the electrolysis rate of water.
[0058] In the electric scale removal device of the present application, the current is preferably as small as possible, because only a very small amount of water needs to be electrolyzed to generate hydroxide ions sufficient to precipitate and remove calcium ions and magnesium ions, and there is no need to electrolyze a large amount of water to generate hydrogen and oxygen. Therefore, a small current is desired to reduce the energy consumption of scale removal.
[0059] Compared with the prior art, the present application has the following beneficial effects: 1. The present device uses a porous insulating filler layer as a functional partition layer, with a cathode and an anode integrated on both sides respectively, forming a composite electrode unit with a unique "filler - electrode" integrated structure. Driven by an ultra - low DC working voltage, the migration of hydroxide ions is blocked by controlling the transmission of water through the micropores of the filler. At the same time, with the help of the local gradient diffusion effect generated by the catalytic reaction on the electrode surface and the forced diffusion effect of pumping, the hydroxide ions are diffused into the main body of the water phase in the cathode chamber, promoting the rapid crystallization and precipitation of scaling ions in the cathode region and reducing the hardness of water.
[0060] 2. In addition, the device of the present application can also treat water containing chloride ions. During the electrolysis of chloride ions into chlorine gas and removal at the anode, an acidic micro - environment (pH < 7) is formed in the anode chamber due to the oxygen evolution / chlorine evolution reaction. Moreover, the alkaline water obtained at the cathode and the acidic water obtained at the anode of the present application are neutralized outside the reaction chamber. This enables the chlorine gas electrolyzed and generated at the anode in the anode chamber to be efficiently purged and removed by the stripping method in an acidic water environment without additional acidification treatment. And the acidic water obtained in the anode chamber contains dissolved chlorine and has a self - bacteriostatic effect.
[0061] 3. In a preferred embodiment, the present application adopts an alternating current mode. After the periodic inversion of the cathode and anode, in-situ cleaning of scale can be achieved to realize self-cleaning of the electrolyzed water cathode, eliminating the need to set up an ultrasonic cleaner for scale removal.
[0062] 4. The solution of the present application not only abandons the external addition of traditional scale inhibitors and acid-base agents, avoiding the risk of chemical residue pollution from the source, but also inhibits the growth of microorganisms through the simultaneously generated active chlorine substances, solving the industry problem of the mutual reinforcement of scaling and corrosion.
[0063] 5. In a preferred embodiment, in the composite electrode unit of the present application, the electrolyzed water cathode, the porous insulating filler layer, and the electrolyzed water anode are in close contact with each other. In this way, due to the extremely small direct distance between the cathode and anode, the electrolyte resistance between the cathode and anode can be reduced, and the energy consumption of the system operation can be decreased. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 It is a schematic structural diagram of the electrochemical water treatment system of the present application.
[0065] Figure 2 It is a schematic structural diagram of a conventional electrolyzed water device.
[0066] LIST OF REFERENCE NUMERALS: 1 - Power supply; 2 - Electrolyzed water cathode; 3 - Electrolyzed water anode; 4 - Porous insulating filler layer; 5 - Reaction chamber; 6 - Raw water tank; 7 - Reclaimed water tank; 8 - Anode chamber inlet pipeline; 9 - Cathode chamber inlet pipeline; 10 - Anode chamber outlet pipeline; 11 - Cathode chamber outlet pipeline; 12 - Filter device; 01 - Membrane; 02 - Cathode chamber of the conventional electrolyzed water device; 03 - Anode chamber of the conventional electrolyzed water device. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0067] The present invention will be described below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For the experimental methods without specific conditions indicated in the embodiments, they are generally carried out according to the conventional conditions and the conditions described in the manuals, or according to the conditions recommended by the manufacturers. For the general equipment, materials, reagents, etc., if not otherwise specified, they can all be obtained from commercial channels. The raw materials required in the following examples and comparative examples are all commercially available.
[0068] This application proposes a low-energy electrochemical water treatment method based on the synergistic effect of ion blocking and forced diffusion. The core lies in the innovative design of a gapless electrolysis unit composed of a porous insulating filler layer 4 and a catalytic electrode. This device uses a hydrophobic porous insulating filler layer 4 as a functional separation layer, with a highly catalytically active mesh cathode and anode integrated on both sides, forming a unique "filler-electrode" integrated structure. Driven by an ultra-low DC voltage of 1.5V to 30V, the directional migration of hydroxide ions is blocked through the controlled transport in the micropores of the filler, causing them to precipitate with calcium and magnesium ions; at the same time, by means of the local forced diffusion effect generated by the rapid flow of the water entering the cathode chamber at the electrolyzed water cathode, the scaling ions are promoted to rapidly crystallize and precipitate in the water body. During the electrolysis process, the acidic microenvironment (pH < 7) formed in the anode chamber due to the oxygen evolution / chlorine evolution reaction enables the electrolytically generated chlorine gas to be efficiently purged and removed by stripping without additional acidification treatment. This dual-action mechanism enables the system to efficiently remove hardness ions in the circulating water while maintaining a low energy consumption level, and significantly improves the cooling water concentration capacity, thereby significantly reducing the makeup water volume and sewage discharge volume, and ultimately achieving high energy efficiency and near-zero emissions in the industrial water treatment process.
[0069] The preferred technical solutions are as follows: The porous insulating filler layer 4 can be made of hydrophobic resin materials. The porous insulating filler layer 4 can be an open-cell foam plastic layer or an open-cell foam plastic layer, including but not limited to polyethylene polymer layers, such as polyethylene layers, polystyrene layers, polyvinyl chloride layers, polypropylene layers, polyurethane layers and other substrates. The porosity of the porous insulating filler layer 4 is 1% - 98% (preferably 30% - 60%), the thickness is 0.05 - 5 mm (preferably 0.1 - 2 mm), and the COD (chemical oxygen demand) tolerance range is 0 - 10000 mg / L. The pore size distribution of the porous insulating filler layer 4 is 0.1 - 500 microns. Similar effects are achieved when the porous insulating filler layer 4 selects a foam plastic layer doped with inorganic substances such as iron oxides.
[0070] The porous insulating filler layer 4 can also use other organic materials, including but not limited to polyamide layers, polyethersulfone layers, polypropylene hollow fiber layers, polytetrafluoroethylene composite layers, sulfonated polyether ether ketone layers, polybenzimidazole layers, polyimide layers.
[0071] The electrolyzed water cathode 2 is selected from one or a combination of the following materials: nickel wire mesh (mesh number 50 - 200), stainless steel mesh (304 / 316L), nickel foam (porosity 85% - 95%), nickel wire mesh loaded with Raney nickel catalyst (loading amount 5% - 20%), platinum, titanium.
[0072] The electrolytic water anode 3 is a titanium-based composite coating electrode or platinum, graphene, etc. Among them, the titanium-based composite coating electrode is selected from one or more of titanium-plated iridium oxide (IrO2-Ti), titanium-plated ruthenium oxide (RuO2-Ti), and iridium tantalum mixed oxide coating (IrO2-Ta2O5-Ti).
[0073] The self-cleaning function integrated in the device is as follows: The electrode polarity is periodically switched through a square-wave alternating current regulation system. The switching frequency of the square-wave alternating current is 0.00001~0.1 Hz. Preferably, the switching frequency of the square-wave alternating current is 0.0001~0.05 Hz. The peak-to-valley ratio of the square-wave alternating current is (100:1)~(1:100). Preferably, the peak-to-valley ratio of the square-wave alternating current is 10:1~1:10. Of course, it can also be other forms of alternating current.
[0074] The water flow rates in the cathode chamber and the anode chamber are 0.1~1.0 m / s, preferably 0.3~0.5 m / s, to ensure that the ion mass transfer rate ≥ 5×10 -5 mol / (m 2 ·s).
[0075] The flow channels of the cathode chamber and the anode chamber are designed as a serpentine or baffle plate structure to extend the hydraulic retention time to 10~30 seconds.
[0076] The electrochemical water treatment method is applicable to the circulating water treatment with a calcium and magnesium ion concentration of 10~20000 mg / L.
[0077] The present invention will be further described below in conjunction with the drawings and embodiments.
[0078] The circulating water electrochemical water treatment device proposed by the present invention realizes low-energy consumption and high-efficiency removal of circulating water hardness ions and self-cleaning function through the coupling of innovative structural design and reaction mechanism. The following is a systematic elaboration from three dimensions: device structure, treatment process, and reaction mechanism: First, as Figure 1 , the device is composed of the following core components: Reaction chamber 5: It uses a carbon steel or stainless steel matrix, and the outer surface is coated with an epoxy resin anti-corrosion layer, which has both electrical insulation and corrosion resistance characteristics. The inside of the reaction chamber 5 is divided into an anode chamber and a cathode chamber by a composite electrode unit. The anode chamber and the cathode chamber are respectively provided with an anode chamber inlet pipeline 8, a cathode chamber inlet pipeline 9, an anode chamber outlet pipeline 10, a cathode chamber outlet pipeline 11, and a filtering device 12 to form independent fluid channels. The filtering device 12 is used to intercept crystal suspensions.
[0079] Figure 1 Only two side plates of the reaction chamber 5 are shown in
[0080] The system further includes: a raw water tank 6 and a recycled water tank 7. The raw water tank 6 is communicated with the anode chamber through an anode chamber inlet pipeline 8, the raw water tank 6 is communicated with the cathode chamber through a cathode chamber inlet pipeline 9, the recycled water tank 7 is communicated with the anode chamber through an anode chamber outlet pipeline 10, and the recycled water tank 7 is communicated with the cathode chamber through a cathode chamber outlet pipeline 11.
[0081] Composite electrode unit: integrally formed by an electrolyzed water cathode 2, an electrolyzed water anode 3, and a porous insulating filler layer 4.
[0082] Electrolyzed water cathode 2: made of a nickel-based high specific surface area material (such as nickel wire mesh, nickel foam, or a metal skeleton loaded with Raney nickel catalyst) or one or more of platinum, titanium, and stainless steel mesh. Its three-dimensional pore structure can strengthen the diffusion of hydroxide ions and the attachment of crystals.
[0083] Electrolyzed water anode 3: selected from one or more of a titanium-based coated electrode (such as titanium coated with iridium oxide, titanium coated with ruthenium oxide, or an iridium tantalum composite coating), platinum, and a graphene-doped electrode, etc., with low chlorine evolution, oxygen evolution overpotential, and acid corrosion resistance.
[0084] Porous insulating filler layer 4: prepared from a hydrophobic resin. The porosity of the hydrophobic resin is 3% - 98%, and the thickness is 0.05 - 5 mm, enabling the controlled penetration of water molecules to ensure the stability of the ion concentration gradient in the anode and cathode chambers.
[0085] The length and height of the composite electrode unit are the same as those of the side plate of the reaction chamber 5. This matching design of equal height and equal length enables the composite electrode unit to be physically in contact with the reaction chamber 5 without gaps, avoiding the direct mixing of alkaline water and acidic water in the anode and cathode chambers within the reaction chamber 5. The design of the composite electrode unit reduces the distance between the anode and cathode, effectively eliminating the resistance loss of the electrode spacing in the traditional reaction chamber.
[0086] The power supply 1 is a square wave alternating current regulation system, specifically using an integrated low-frequency square wave generator with a frequency of 0.00001 - 0.1 Hz and an adjustable peak-to-valley ratio range of 100:1 - 1:100. The purpose of the square wave alternating current regulation system is to generate a dynamic acid-base environment through periodic polarity reversal to trigger the self-peeling of scale on the electrode surface.
[0087] Second, the circulating water treatment process Raw liquid supply stage: The circulating water containing high concentrations of calcium and magnesium ions (calcium ion / magnesium ion concentration 10 - 20000 mg / L) is stored in the raw water tank 6 and pumped into the anode chamber and the cathode chamber of the reaction chamber 5 through the anode chamber inlet pipeline 8 and the cathode chamber inlet pipeline 9 at a flow rate of ≥0.1 m / s respectively.
[0088] Preferably, one ends of the anode chamber inlet pipeline 8 and the cathode chamber inlet pipeline 9 are respectively arranged at the bottoms of the electrodes in the anode chamber and the cathode chamber, and the pipeline openings face the electrode surfaces, so as to form a swirling flow by using fluid inertia to cover the entire electrode surface.
[0089] Preferably, one ends of the anode chamber outlet pipeline 10 and the cathode chamber outlet pipeline 11 are respectively arranged at the tops of the anode chamber and the cathode chamber, which is conducive to the rapid escape of the electrolytically generated gas, avoiding bubbles adhering to the electrode surface and reducing the reaction efficiency. Preferably, the outlet pipeline and the inlet pipeline form a diagonal design. For example: the outlet pipeline opening is at the top on the side far from the electrode or the pipeline opening is at the top on the side of the electrode. This can enable the water flow to continuously wash the electrode surface in the flow path from the inlet to the outlet. At the same time, the residence time of the water flow in the chamber is prolonged. At the same time, by controlling the water flow rate, forced convection is formed in the anode chamber and the cathode chamber. The forced convection design can inhibit the thickening of the boundary layer and enhance the ion mass transfer efficiency.
[0090] Third, the electrochemical treatment stage Typically, under the drive of a 1.5V ultra-low DC voltage, different electrochemical reactions occur in the anode and cathode chambers.
[0091] Cathode chamber: Electrolyze water to generate hydroxide ions (2H2O + 2e - →H2↑ + 2OH - ), and the alkaline environment promotes the conversion of bicarbonate ions to carbonate ions (HCO3 - + OH - →CO3 2- + H2O), and then combines with calcium ions / magnesium ions to form calcium carbonate, magnesium hydroxide and magnesium carbonate crystals.
[0092] Anode chamber: Chloride ions are oxidized to generate active chlorine (2Cl - →Cl2↑ + 2e - ), and at the same time water is electrolyzed to generate hydrogen ions (H2O → ½O2↑ + 2H + + 2e - ), and the acidic environment inhibits secondary scaling and realizes synchronous sterilization and algae inhibition.
[0093] The meaning of secondary scaling is as follows: Cathode reaction: Electrolyze water to generate hydroxide ions (2H2O + 2e - →H2↑ + 2OH - ), the pH in the cathode region increases (alkaline), which promotes the formation of calcium ions / magnesium ions precipitation (conventional scaling).
[0094] If the micron-scale precipitates generated in the cathode region diffuse with the water flow to the anode region, they may redissolve in a neutral or weakly acidic environment. However, if the anode environment is not properly controlled (such as the pH is not low enough), these particles may be redeposited on the anode electrode surface due to electrostatic adsorption or turbulent perturbation, forming "secondary scaling".
[0095] Regenerated water recovery stage: The treated anodic regenerated water (pH 2 - 4, enriched with hydrogen ions) and cathodic regenerated water (pH 10 - 12, containing crystalline suspended solids) are respectively pumped into the regenerated water tank 7 through the anodic chamber outlet pipeline 10 and the cathodic chamber outlet pipeline 11 (where the crystalline suspended solids flowing out of the cathodic chamber will be intercepted and filtered into the device 12 and will no longer contact the anodic regenerated water). Through the neutralization reaction (H + + OH - → H2O), the electrical neutrality is restored, and the precipitates are resourcefully utilized after solid-liquid separation.
[0096] Fourth, self-cleaning and energy efficiency optimization mechanism Dynamic scaling removal: The square-wave alternating current system of the power supply 1 periodically switches the electrode polarities, and uses the locally strong acidic (hydrogen ions in the anode chamber) or strong alkaline (hydroxide ions in the cathode chamber) environment at the moment of polarity inversion to dissolve the microcrystalline scale layer on the electrode surface, realizing in-situ self-cleaning (scale layer stripping efficiency ≥ 95%).
[0097] Energy consumption control strategy: The gapless electrode design combined with the square-wave power supply mode reduces the concentration polarization loss, and the comprehensive energy consumption is reduced by 20% - 70% compared with the existing technology. It consumes 2 - 5 kWh of electricity to remove each kilogram of hardness (calculated as calcium carbonate).
[0098] Among them, the general formula for calculating the energy consumption based on the generation of hydroxide ions and the precipitation of calcium ions is as follows: When the reaction generates hydroxide ions (hydroxide) through electrolysis of water and then combines with calcium ions to precipitate (such as generating calcium hydroxide or calcium carbonate), the steps for calculating the theoretical energy consumption for removing each kilogram of hardness (calculated as calcium carbonate) are as follows: 1. Reaction path and electron transfer relationship Cathodic reaction (generation of hydroxide ions): 2H2O + 2e - → H2↑ + 2OH - Precipitation reaction (removal of calcium ions): Ca 2+ + 2OH - → Ca(OH)2↓ or Ca 2+ + CO3 2- → CaCO3↓ Electron transfer relationship: 2 moles of electrons are required to remove 1 mole of calcium ions.
[0099] 2. Calculation steps: Moles of calcium carbonate removed: Moles = m × 1000 / M (calcium carbonate) = 1000m / 100.08 ≈ 10m (mol) where m is the hardness mass treated, in kg as calcium carbonate.
[0100] Theoretically required electricity: Q 理论 = n × moles × F = 2 × 10m × 96485 (C) where n is the number of electrons transferred and F is the Faraday constant.
[0101] Theoretical energy consumption (electric energy = electricity × voltage): E 理论 = Q 理论 × V / (3.6 × 10 6 )(kWh) Taking Example 1 as an example: The amount of hardness removed (as calcium carbonate) m = 1000L × 1000mg / L × 95% = 0.95 kg; The single - stage voltage applied V = 4.4V; The single - stage voltage is the voltage applied between the anode and cathode of the same composite electrode unit. There is one composite electrode unit in each reaction chamber 5. The reaction chambers 5 can be connected in series, also called multi - stage series. The embodiments of this application are all single - stage reaction chambers 5.
[0102] Theoretical energy consumption = 2 × 10 × 0.95 × 96485 × 4.4 / (3.6 × 10 6 ) ≈ 2.24 kWh; Calculation for removing each kilogram of hardness (as calcium carbonate) in Comparative Patent CN101585569A: Since the voltage is not clearly given in the embodiments of the comparative patent, for the device proposed in Comparative Patent CN101585569A, we learned from the literature that its typical voltage range is 12 - 24V. Taking the lowest voltage of 12V as an example (for treating 1 kg of calcium carbonate): Theoretical energy consumption = 2 × 10 × 1 × 96485 × 12 / 3.6 × 10 6 ≈ 6.43 kWh.
[0103] The following provides examples to illustrate the effects of this application. The test materials of this application, such as the materials used for the electrodes and the porous insulating filler layer 4, can be obtained by purchase or self - made by existing methods. The preparation method of the porous insulating filler layer 4 of this application is a conventional process. When the porous insulating filler layer 4 is a polymer material, the solution casting method is used. When the porous insulating filler layer 4 is a material containing polymers and inorganic substances, the solution casting method is used after mixing the two kinds of particles. When the porous insulating filler layer 4 is an inorganic material, the bonding and pressing method is used.
[0104] The hardness of water or calcium and magnesium ions in this application is calculated as calcium carbonate. Example 1
[0105] 1. Treatment object: 1 ton (1000 L) of concentrated circulating water stored in the raw water tank 6, with an initial calcium and magnesium ion concentration (calculated as calcium carbonate) of 1000 mg / L.
[0106] 2. Device configuration: Electrode system: The electrolyzed water anode 3 uses a titanium-based iridium oxide coated electrode (IrO2 loading of 2.5 mg / cm²), and the electrolyzed water cathode 2 uses a nickel foam electrode (porosity of 85%); Porous insulating filler layer 4: Polyethylene-polyamide composite layer (porosity of 60%, thickness of 2 mm, pore diameter of 0.1 - 0.5 μm), with a sulfonated modification layer on the surface.
[0107] The preparation method of the polyethylene-polyamide composite layer is as follows: (1) Add 12.0 g of polyamide (PA6) to 108.0 mL of ortho-dichlorobenzene, heat in an oil bath at 160 °C, and mechanically stir (300 rpm) for 2 hours until completely dissolved to form a clear solution with a solid content of 10.0 wt%.
[0108] (2) Cool the PA6 solution to 100 °C, add 6.0 g of high-density polyethylene (HDPE) particles in batches, heat up to 140 °C at a rate of 1 °C per minute, and perform high-speed shear dispersion at 140 °C at 800 rpm for 1.5 hours.
[0109] (3) Add 2.52 g of n-octanol at 140 °C and stir at 500 rpm for 30 minutes until completely dispersed.
[0110] (4) Pour the homogeneous high-temperature solution into a preheated Teflon mold at 100 °C (mold depth: 2.5 mm).
[0111] (5) Control the cooling rate (first slow cool to 80 °C at a rate of 0.1 °C per minute, then naturally cool to room temperature), and induce phase separation and solvent evaporation to form pores.
[0112] (6) Demold after cooling to below 30 °C.
[0113] (7) Immerse in concentrated sulfuric acid with a mass fraction of 98% for 40 min for sulfonation modification, and dry in a vacuum oven at 60 °C for 12 h after immersion.
[0114] 3. Operation process: (1) Feeding stage: Inject the concentrated circulating water into both electrode chambers at a flow rate of 0.5 m / s through a booster pump.
[0115] (2)Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 4.4 V), current density 200 A / m², frequency 0.0033 Hz (cycle 300 s / 5 minutes), peak-to-valley ratio 10:1), and run for 4 cycles (total duration 1200 s); (3)Recycled water discharge: Open the outlet pipeline 10 of the anode chamber and the outlet pipeline 11 of the cathode chamber, and pump the recycled water into the recycled water tank 7 at a flow rate of 1.0 m / s.
[0116] (4)Circulating treatment: Repeat the feeding-treatment-drainage steps 5 times, with a cumulative operation of 20 cycles and a total treatment duration of 6000 s (100 minutes).
[0117] 4. Treatment effect: Raw water tank 6: All 1000 L of concentrated circulating water has been treated; Effluent water quality: Collect 1000 L of recycled water, and the calcium and magnesium ion concentration is reduced to 50 mg / L, with a removal rate of 95%.
[0118] Actual energy consumption data: The initial cell voltage is 4.5 V, and the cell voltage rises to 4.7 V (rise value 0.2 V) at the end of the treatment cycle. The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 2.5 kWh, which is 61.1% lower than that of the comparative patent CN101585569A (6.43 kWh). Example 2
[0119] High-temperature corrosion-resistant scenario: 1. Treatment object: 1.2 tons (1200 L) of high-temperature concentrated circulating water (temperature 80 degrees Celsius), with an initial hardness (calculated as calcium carbonate) of 1200 mg / L.
[0120] 2. Device configuration: Electrode system: The electrolyzed water anode 3 uses a titanium-plated ruthenium oxide electrode with a ruthenium loading of 1.8 mg / cm²; the electrolyzed water cathode 2 uses a nickel wire mesh porous electrode; Porous insulating filler layer 4: Polyphenylene sulfide-aluminum oxide composite layer (porosity 70%, thickness 1.5 mm, pore diameter 0.2 - 0.8 microns).
[0121] The preparation method of the polyphenylene sulfide-aluminum oxide composite layer is as follows: (1)Under nitrogen protection, add 20.0 g of polyphenylene sulfide (PPS) particles to 180 mL of N-methylpyrrolidone (NMP), heat to 216 degrees Celsius, and stir vigorously (800 rpm) until completely dissolved; (2)Cool down to 180 degrees Celsius, add 30.0 g of aluminum oxide (Al2O3) powder, and perform ultrasonic treatment for 30 min to ensure good dispersion; (3)Add 3.0 g of polyethylene glycol 400 and disperse it evenly by ultrasonic treatment; (4) Rapidly pour the uniform high-temperature slurry into a stainless-steel mold preheated to 150 °C (mold depth: 1.65 mm); (5) Place it in an oven, first maintain at 180 °C for 1.5 h (to prevent rapid cooling and crystallization), then cool down to 100 °C at a rate of 0.8 °C per minute, and finally volatilize the residual solvent to room temperature under ventilation conditions; (6) Demold.
[0122] 3. Operation process: (1) Feeding stage: Concentrated circulating water is injected at a flow rate of 0.6 m / s; (2) Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 4.8 V, frequency 0.0017 Hz (period 600 s / 10 minutes), peak-to-valley ratio 8:1), run for 6 cycles (total duration 3600 s), current density 150 A / m²; (3) Reclaimed water discharge: Discharge the reclaimed water at a flow rate of 0.8 m / s.
[0123] (4) Circulation treatment: Repeat 6 times, with a total of 36 cycles, and the total treatment duration is 21,600 s (6 hours).
[0124] 4. Treatment effect: Raw water tank 6: 1200 L of concentrated circulating water treatment is completed; Effluent water quality: Collect 1200 L of reclaimed water, the hardness is reduced to 72 mg / L, and the rejection rate is 94%.
[0125] Actual energy consumption data: The initial cell voltage is 4.9 V, and the cell voltage rises to 5.2 V at the end of the treatment cycle (rise value 0.3 V). The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 3.8 kWh, which is 40.9% lower than that of the comparative patent CN101585569A (6.43 kWh). Example 3
[0126] Low-cost environmental protection solution: 1. Treatment object: 800 L of low-concentration concentrated circulating water, hardness (calculated as calcium carbonate) 300 mg / L.
[0127] 2. Device configuration: Electrode system: The electrolyzed water anode 3 uses an iridium-tantalum mixed oxide, and the electrolyzed water cathode 2 uses a Raney nickel electrode supported by a nickel wire mesh; Porous insulating filler layer 4: Polypropylene hollow fiber-silica composite layer (porosity 1%, thickness 0.05 mm, pore diameter 0.3 - 500 μm), with a quaternary ammonium group modified layer on the surface.
[0128] The preparation method of the polypropylene hollow fiber-silica composite layer is as follows: (1) Dissolve 15.0 g of polypropylene (PP) pellets in 135 mL of decalin at 140 °C to form a solution; (2) Cool down to 100 °C, add 4.5 g of silica nanoparticles, and stir vigorously and disperse uniformly by ultrasonic treatment; (3) Add 1.5 g of cyclohexane; (4) Lay the polypropylene hollow fiber (PPHF) fabric flat on the bottom of the mold (mold depth: 1 mm); (5) Pour the mixed slurry while it is hot (100 °C) onto the PPHF layer to ensure sufficient infiltration; (6) Naturally cool to room temperature to evaporate the solvent; (7) Demold; (8) Immerse it in an ethanol solution of 5 wt% quaternized silane for 60 minutes and cure at 80 °C for 1 hour.
[0129] 3. Operation process: (1) Feeding stage: Concentrated circulating water is injected at a flow rate of 0.3 m / s; (2) Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 30 V, frequency 0.0011 Hz (period 900 s / 15 minutes), peak-to-valley ratio 12:1), run for 3 cycles (total duration 2700 s), and the current density is 1000 A / m²; (3) Discharge of reclaimed water: Discharge the reclaimed water at a flow rate of 0.8 m / s; (4) Circulation treatment: Repeat 13 times, with a total of 40 cycles, and the total treatment duration is 108,000 s (30 hours).
[0130] 4. Treatment effect: Raw water tank 6: 800 L of circulating water treatment is completed; Effluent water quality: Collect 800 L of reclaimed water, the hardness is reduced to 15 mg / L, and the interception rate is 95%.
[0131] Actual energy consumption data: The initial cell voltage is 30.1 V, and the cell voltage rises to 30.4 V at the end of the treatment cycle (the increase value is 0.3 V). The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 4.0 kWh, which is 37.7% lower than that of the comparative patent CN101585569A (6.43 kWh). Example 4
[0132] Pretreatment of high-salt seawater: 1. Treatment object: 2000 L of seawater desalination pretreatment liquid, with a hardness (calculated as calcium carbonate) of 800 mg / L.
[0133] 2. Device configuration: Electrode system: The anode 3 for electrolyzing water uses a platinum-carbon electrode, and the cathode 2 for electrolyzing water uses a nickel foam electrode; Porous insulating filler layer 4: Polytetrafluoroethylene-silicon carbide composite layer (porosity 65%, thickness 2.2 mm, pore diameter 0.5 - 500 microns); The preparation method of the polytetrafluoroethylene-silicon carbide composite layer is as follows: (1) Dilute 100 mL of polytetrafluoroethylene dispersion with a solid content of 60 wt% (solvent is water) to a solid content of 24 wt% with deionized water; (2) Add 45 g of silicon carbide (SiC) powder, and stir vigorously and disperse evenly by ultrasonic; (3) Add double pore-forming agents: Add 30.0 g of NaCl particles with a particle size of 200 microns and 15.0 g of sucrose powder with a particle size of 5 microns; (4) Pour the mixed slurry into a mold (mold depth: 2.5 mm); (5) First, dry slowly at room temperature (to prevent cracking), and then sinter step by step in an oven. The temperature and holding time are as follows: hold at 60 °C for 12 hours, hold at 100 °C for 12 hours, hold at 200 °C for 2 hours, hold at 327 °C for 1 hour; (6) Demold after cooling to room temperature.
[0134] 3. Operating process: (1) Feeding stage: Concentrated circulating water is injected at a flow rate of 0.7 m / s; (2) Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 4.2 V, frequency 0.00083 Hz (cycle 1200 s / 20 minutes), peak-to-valley ratio 5:1), run for 5 cycles (total duration 6000 s), and the current density is 300 A / m²; (3) Discharge of reclaimed water: Discharge reclaimed water at a flow rate of 1.0 m / s.
[0135] (4) Circulating treatment: Repeat 12 times, with a total of 60 cycles, and the total treatment duration is 72,000 s (20 hours).
[0136] 4. Treatment effect: Raw water tank 6: 2000 L of pretreatment liquid has been processed; Effluent water quality: Collect 2000 L of reclaimed water, the hardness is reduced to 64 mg / L, and the rejection rate is 92%.
[0137] Actual energy consumption data: The initial cell voltage is 4.4 V, and the cell voltage rises to 4.6 V (rise value 0.2 V) at the end of the treatment cycle. The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 3.7 kWh, which is 42.4% lower than that of the comparative patent CN101585569A (6.43 kWh). Example 5
[0138] 1. Treatment object: 2 tons (2000 L) of concentrated circulating water in the cooling tower circulating water system, with an initial hardness (calculated as calcium carbonate) of 800 mg / L.
[0139] 2. Device configuration: Electrode system: The electrolyzed water anode 3 uses a platinum sheet electrode (thickness 0.5 mm, surface area 0.2 m²), and the electrolyzed water cathode 2 uses a platinum mesh electrode (porosity 75%, pore diameter 1.0 mm); Porous insulating filler layer 4: Polyvinylidene fluoride-zirconia composite layer (porosity 55%, thickness 1.5 mm, pore diameter 0.2 - 0.8 μm).
[0140] The preparation method of the polyvinylidene fluoride-zirconia composite layer is as follows: (1) Dissolve 20.0 g of polyvinylidene fluoride (PVDF) particles in 180 mL of dimethylformamide (DMF), and heat and stir at 50 °C until a clear solution is obtained; (2) Add 6.0 g of zirconia (ZrO2) powder, and stir vigorously and disperse evenly by ultrasonic waves; (3) Add 4.0 g of polyethylene glycol 1000; (4) Pour the mixed slurry into a mold (mold depth: 1.6 mm); (5) Keep the mold at a constant temperature of 50 °C for 24 hours; (6) After the solvent has basically evaporated, raise the temperature to 90 °C to further remove the residual solvent; (7) Cool to room temperature and demold.
[0141] 3. Operation process: (1) Feeding stage: Inject the concentrated circulating water into the two electrode chambers at a flow rate of 0.6 m / s.
[0142] (2) Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 5.0 V, frequency 0.00067 Hz (cycle 1500 s / 25 minutes), peak-to-valley ratio 10:1), run for 3 cycles (total duration 4500 s), and the current density is 400 A / m²; (3) Reclaimed water discharge: Open the outlet pipeline 10 of the anode chamber and the outlet pipeline 11 of the cathode chamber, and pump the reclaimed water into the reclaimed water tank 7 at a flow rate of 1.0 m / s; (4) Circulation treatment: Repeat 15 times, with a cumulative operation of 45 cycles and a total treatment duration of 67,500 s (18.75 hours).
[0143] 4. Treatment effect: Raw water tank: All 2000 L of concentrated circulating water has been treated; Effluent quality: 2000 L of reclaimed water was collected, and the calcium and magnesium ion concentration decreased to 32 mg / L, with a removal rate of 96%.
[0144] Actual energy consumption data: The initial cell voltage was 5.5 V, and at the end of the treatment cycle, the cell voltage rose to 5.7 V (a rise value of 0.2 V). The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) was 4.4 kWh, which was 31.5% lower than that of the comparative patent CN101585569A (6.43 kWh). Example 6
[0145] 1. Treatment object: 1.5 tons (1500 L) of industrial boiler return water, with an initial calcium and magnesium ion concentration (calculated as calcium carbonate) of 1200 mg / L.
[0146] 2. Device configuration: Electrode system: The electrolytic water anode 3 used a platinum-coated titanium electrode (platinum layer thickness 50 μm, surface area 0.15 m²), and the electrolytic water cathode 2 used a porous platinum electrode (porosity 80%, pore diameter 0.5 mm); Porous insulating filler layer 4: Sulfonated polyether ether ketone - polybenzimidazole composite layer (porosity 98%, thickness 5 mm, pore diameter 0.1 - 0.3 μm).
[0147] The preparation method of the sulfonated polyether ether ketone - polybenzimidazole composite layer is as follows: (1) Dissolve 5.0 g of sulfonated polyether ether ketone (SPEEK) and 5.0 g of polybenzimidazole (PBI) in 45 mL of dimethyl sulfoxide (DMSO) respectively to obtain their respective clear solutions; (2) Mix the above two solutions and stir strongly to ensure uniformity; (3) Add double pore - forming agents: ethylene glycol: 1.0 g, 1 - propanol: 0.5 g; (4) Pour the mixed solution into a mold (mold depth: 5.5 mm); (5) Place it in an oven at a constant temperature (70 °C) with good ventilation to slowly volatilize the solvent (for 3 days); (6) After the solvent has completely volatilized, raise the temperature to 110 °C for further drying and curing; (7) Cool to room temperature and demold.
[0148] 3. Operating procedure: (1) Feeding stage: Inject the concentrated circulating water into the two - electrode chambers at a flow rate of 0.4 m / s through a booster pump; (2) Electrochemical treatment: Apply a square - wave alternating current (single - stage voltage 3.8 V, frequency 0.0021 Hz (cycle 480 s / 8 minutes), peak - to - valley ratio 10:1), run for 5 cycles (total duration 2400 s), and the current density is 250 A / m²; (3) Reclaimed water discharge: Open the outlet pipeline 10 of the anode chamber and the outlet pipeline 11 of the cathode chamber, and pump the reclaimed water into the reclaimed water tank 7 at a flow rate of 0.8 m / s; (4) Circulating treatment: Repeat 9 times, accumulate 48 operation cycles, and the total treatment duration is 115,200 s (32 hours).
[0149] 4. Treatment effect: Raw water tank: All 1500 L of concentrated circulating water has been treated; Effluent water quality: Collect 1500 L of reclaimed water, the calcium and magnesium ion concentration drops to 24 mg / L, and the removal rate is 98%.
[0150] Actual energy consumption data: The initial cell voltage is 3.9 V, and the cell voltage rises to 4.1 V (rise value 0.2 V) at the end of the treatment cycle. The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 3.8 kWh, which is 40.9% lower than the comparative patent CN101585569A (6.43 kWh). Example 7
[0151] 1. Treatment object: 3 tons (3000 L) of central air-conditioning circulating water, and the initial calcium and magnesium ion concentration (calculated as calcium carbonate) is 600 mg / L.
[0152] 2. Device configuration: Electrode system: The electrolytic water anode 3 uses a platinum-ruthenium oxide composite electrode (RuO2 loading of 3.0 mg / cm²), and the electrolytic water cathode 2 uses a platinum-coated stainless steel mesh electrode (porosity of 90%); Porous insulating filler layer 4: Polyimide-mullite composite layer (porosity of 65%, thickness of 2.2 mm, pore diameter of 0.3 - 1.0 μm).
[0153] The preparation method of the polyimide-mullite composite layer is as follows: (1) Dissolve 20.0 g of polyimide precursor polyamic acid (PAA) in 180 mL of N-methylpyrrolidone (NMP); (2) Add 30.0 g of mullite powder, and stir and disperse evenly by strong stirring and ultrasonic treatment; (3) Add 10.0 g of polyethylene glycol 2000; (4) Pour the mixed slurry into a mold (mold depth: 2.35 mm); (5) Place the mold in a ventilated oven and perform programmed temperature rise imidization: Keep at 80 °C for 1 hour, 135 °C for 1 hour, 200 °C for 1 hour, 250 °C for 1 hour, and 300 °C for 1 hour.
[0154] (6) Naturally cool to room temperature and demold.
[0155] 3. Operating Process: (1) Feeding Stage: Concentrated circulating water is injected into both electrode chambers at a flow rate of 0.7 m / s through a booster pump. (2) Electrochemical Treatment: Apply square-wave alternating current (single-stage voltage 4.2 V, frequency 0.0014 Hz (period 720 s / 12 minutes), peak-to-valley ratio 10:1), run for 4 cycles (total duration 2880 s), and the current density is 350 A / m². (3) Reclaimed Water Discharge: Open the outlet pipeline 10 of the anode chamber and the outlet pipeline 11 of the cathode chamber, and pump the reclaimed water into the reclaimed water tank 7 at a flow rate of 0.9 m / s. (4) Circulating Treatment: Repeat 4 times, with a total of 16 cycles, and the total treatment duration is 46,080 s (12.8 hours).
[0156] 4. Treatment Effect: Raw Water Tank: All 3000 L of concentrated circulating water has been completely treated. Effluent Water Quality: Collect 3000 L of reclaimed water, the calcium and magnesium ion concentration drops to 30 mg / L, and the removal rate is 95%.
[0157] Actual Energy Consumption Data: The initial cell voltage is 4.5 V, and the cell voltage rises to 4.7 V (rise value 0.2 V) at the end of the treatment cycle. The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 4.1 kWh, which is 36.2% lower than that of the comparative patent CN101585569A (6.43 kWh). Example 8
[0158] 1. Treatment Object: 0.8 tons (800 L) of geothermal reinjection water, with an initial calcium and magnesium ion concentration (calculated as calcium carbonate) of 1500 mg / L.
[0159] 2. Device Configuration: Electrode System: The electrolyzed water anode 3 uses a nano-platinum black electrode (specific surface area 120 m² / g), and the electrolyzed water cathode 2 uses a platinum-coated carbon fiber electrode (porosity 85%); Porous Insulating Filler Layer 4: Polyimide-silicon nitride composite layer (porosity 50%, thickness 1.2 mm, pore diameter 0.1 - 0.4 μm), with an amino-modified layer on the surface.
[0160] The preparation method of the porous insulating filler layer 4 is as follows: (1) Dissolve 20.0 g of polyimide precursor polyamic acid (PAA) in 180 mL of NMP; (2) Add 40.0 g of silicon nitride powder, and stir and disperse evenly with strong stirring and ultrasonic waves; (3) Add 8.0 g of polyethylene glycol 2000; (4) Pour the mixed slurry into a mold (mold depth: 1.5 mm); (5) Place the mold in a ventilated oven and perform programmed temperature rise imidization: maintain at 80 °C for 1 hour, 135 °C for 1 hour, 200 °C for 1 hour, 250 °C for 1 hour, 300 °C for 1 hour; (6) Naturally cool to room temperature and demold; (7) Place the composite layer in a plasma reaction chamber, introduce ammonia gas, and treat it at a power of 100 W for 5 minutes to introduce amino groups on the surface of the polyimide-silicon nitride composite layer.
[0161] 3. Operation process: (1) Feeding stage: Inject concentrated circulating water into the two electrode chambers at a flow rate of 0.3 m / s through a booster pump; (2) Electrochemical treatment: Apply a square wave alternating current (single-stage voltage 4.5 V, frequency 0.00056 Hz (period 1800 s / 30 minutes), peak-to-valley ratio 10:1), run for 6 cycles (total duration 10,800 s), and current density 100 A / m²; (3) Reclaimed water discharge: Open the outlet pipelines 10 of the anode chamber and 11 of the cathode chamber, and pump the reclaimed water into the reclaimed water tank 7 at a flow rate of 0.6 m / s; (4) Circulation treatment: Repeat 16 times, accumulate 100 cycles of operation, and the total treatment duration is 180,000 s (50 hours).
[0162] 4. Treatment effect: Raw water tank: All 800 L of concentrated circulating water has been treated; Effluent water quality: Collect 800 L of reclaimed water, the calcium and magnesium ion concentration drops to 45 mg / L, and the removal rate is 97%.
[0163] Actual energy consumption data: The initial cell voltage is 4.7 V, and the cell voltage rises to 4.9 V at the end of the treatment cycle (rise value 0.2 V). The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 3.0 kWh, which is 53.3% lower than that of the comparative patent CN101585569A (6.43 kWh). Example 9
[0164] 1. Treatment object: 2.5 tons (2500 L) of seawater desalination pretreated water, with an initial calcium and magnesium ion concentration (calculated as calcium carbonate) of 2000 mg / L.
[0165] 2. Device configuration: Electrode system: The electrolyzed water anode 3 uses an iridium oxide electrode, and the electrolyzed water cathode 2 uses a titanium mesh electrode (porosity 95%); Porous insulating filler layer 4: Asbestos layer (porosity 75%, thickness 0.18 mm, pore diameter 1 - 500 microns).
[0166] The preparation method of the asbestos layer is as follows: (1) Protection preparation: Operate in a negative pressure glove box or a dedicated fume hood. Wear a full-body protective suit, goggles, N100 mask, and gloves.
[0167] (2) Pretreatment: Gently dissociate the asbestos fibers into shorter fibers (length 1 - 2 mm) (avoid excessive fragmentation to generate dust), and sieve to remove large impurities.
[0168] (3) Mixing: Weigh 30.0 g of asbestos fibers, add 7.5 g of silica sol, add 9.0 g of pore-forming agent - ammonium bicarbonate powder, add 18 mL of ionized water, adjust to an appropriate consistency (similar to wet mortar), and gently stir and mix evenly with a low-speed stirrer (avoid fiber breakage to generate dust).
[0169] (4) Molding and pre-pressing: Fill the mixed slurry into a mold coated with a release agent (silicone grease) (mold depth: 0.3 mm), and apply a little pre-pressure (0.5 MPa) to remove large air bubbles and make the fibers initially oriented.
[0170] (5) Pressing: Apply pressure (1.5 MPa for 2 minutes). The pressure should not be too high to avoid excessive damage to the pore structure.
[0171] (6) Drying: Carefully demold (low wet strength), place in a well-ventilated area and dry at a low temperature (maintain at 40 °C for 48 hours) until constant weight. The silica sol is initially gelled. There may be a small amount of carbon residue in the heat treatment and the sample after heat treatment. If a completely white color is required, it can be calcined in air at 500 °C for another 1.5 hours.
[0172] (7) Cooling and sealing: Cool to room temperature. The sample must be sealed and stored (double-layer plastic bag).
[0173] 3. Operation process: (1) Feeding stage: Inject concentrated circulating water into the two electrode chambers at a flow rate of 0.9 m / s through a booster pump; (2) Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 1.5 V, frequency 0.0024 Hz (period 420 s / 7 minutes), peak-to-valley ratio 10:1), run for 150 cycles (total duration 63,000 s / 17.5 hours), and current density 1 A / m²; (3) Reclaimed water discharge: Open the outlet pipeline 10 of the anode chamber and the outlet pipeline 11 of the cathode chamber, and pump the reclaimed water into the reclaimed water tank 7 at a flow rate of 1.0 m / s; (4) Circulation treatment: Repeat once, with a cumulative operation of 150 cycles and a total treatment duration of 63,000 s (17.5 hours).
[0174] 4. Treatment effect Raw water tank: All 2500 L of concentrated circulating water has been completely treated; Effluent water quality: 2500 L of reclaimed water is collected, and the calcium and magnesium ion concentration is reduced to 80 mg / L, with a removal rate of 96%.
[0175] Actual energy consumption data: The initial cell voltage is 1.7 V, and the cell voltage rises to 2.2 V (a rise value of 0.5 V) at the end of the treatment cycle. The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 4.2 kWh, which is 34.6% lower than that of the comparative patent CN101585569A (6.43 kWh). Example 10
[0176] 1. Treatment object: 4 tons (4000 L) of circulating cooling water from a petrochemical plant, with an initial calcium and magnesium ion concentration (calculated as calcium carbonate) of 450 mg / L.
[0177] 2. Device configuration: Electrode system: The electrolyzed water anode 3 uses a platinum sheet electrode, and the electrolyzed water cathode 2 uses a platinum-coated graphite electrode (porosity 88%); Porous insulating filler layer 4: Silicon carbide layer (porosity 68%, thickness 2.5 mm, pore diameter 0.2 - 0.6 microns).
[0178] The preparation method of the silicon carbide layer is as follows: (1) Mixing: Weigh 560.0 g of coarse silicon carbide (SiC) powder and 240.0 g of fine silicon carbide (SiC) powder. Add 52 g of Y2O3 sintering aid, 1005 g of 8 wt% polyvinyl alcohol solution, 148 g of nano graphite powder, and 5.0 g of ammonium polyacrylate dispersant.
[0179] (2) Aging: After mixing evenly, seal and age the blank for 24 hours.
[0180] (3) Molding: Dry pressing molding (mold depth: 3.0 mm).
[0181] (4) Drying: Slowly dry in a low-temperature oven (40 °C) to constant weight to prevent cracking.
[0182] (5) Debinding: Keep at 600 °C in a muffle furnace for 2 hours (heating rate 0.5 °C per minute).
[0183] (6) High-temperature sintering under an argon atmosphere (heating from 25 °C to 1000 °C, heating rate 5 °C per minute, and then holding at 1000 °C for 45 minutes).
[0184] (7) Cooling: Cool to room temperature at a cooling rate of 2 °C per minute.
[0185] (8) Bake the sintered sample in an air atmosphere at 700 °C (heating rate: 1 °C per minute) for 3 hours to oxidize and remove the residual graphite pore former, forming the final pores.
[0186] 3. Operating procedure: (1) Feeding stage: Inject the concentrated circulating water into the two electrode chambers at a flow rate of 0.5 m / s through a booster pump. (2) Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 4.8 V, frequency 0.00093 Hz (period 1080 s / 18 minutes), peak-to-valley ratio 10:1), run for 4 cycles (total duration 4320 s), and the current density is 600 A / m². (3) Reclaimed water discharge: Open the outlet pipelines 10 of the anode chamber and 11 of the cathode chamber, and pump the reclaimed water into the reclaimed water tank 7 at a flow rate of 0.8 m / s. (4) Circulating treatment: Repeat 10 times, with a total of 40 cycles, and the total treatment duration is 43,200 s (12 hours).
[0187] 4. Treatment effect: Raw water tank: All 4000 L of concentrated circulating water has been processed. Effluent water quality: Collect 4000 L of reclaimed water, and the calcium and magnesium ion concentration drops to 18 mg / L, with a removal rate of 96%.
[0188] Actual energy consumption data: The initial cell voltage is 5.1 V, and the cell voltage rises to 5.3 V (rise value 0.2 V) at the end of the treatment cycle. The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 4.7 kWh, which is 26.9% lower than that of the comparative patent CN101585569A (6.43 kWh). Example 11
[0189] Continuous method: 1. Treatment object: 10000 L of circulating cooling water from a petrochemical plant, with a calcium and magnesium ion concentration (calculated as calcium carbonate) of 400 mg / L.
[0190] 2. Device configuration: Electrode system: Both the electrolyzed water anode 3 and the electrolyzed water cathode 2 use iridium tantalum oxide-coated titanium mesh electrodes. Porous insulating filler layer 4: Polypropylene-polytetrafluoroethylene composite layer (porosity 68%, thickness 0.2 mm, pore diameter 10 - 200 μm).
[0191] The preparation method of the polypropylene-polytetrafluoroethylene composite layer is as follows: (1) Dissolve 15.0 g of polypropylene (PP) particles in 135 mL of decalin at 145 °C.
[0192] (2) Cool down to 100 degrees Celsius, add 30.0 g of polytetrafluoroethylene aqueous dispersion, and stir vigorously for emulsifying and dispersing.
[0193] (3) Pour the hot emulsion quickly into a preheated (80 degrees Celsius) mold (depth 0.25 mm).
[0194] (4) Gradually increase the temperature in the oven (hold at 80 degrees Celsius for 6 hours, 120 degrees Celsius for 6 hours, 140 degrees Celsius for 3 hours) to remove the solvent and water.
[0195] (5) Cool down to below 40 degrees Celsius and demold.
[0196] 3. Operation process: (1) Feeding stage: Pump cooling water into the two electrode chambers at a flow rate of 0.5 m / s through a booster pump. (2) Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 2.0 V), set the frequency to a positive voltage bias of 950 s, a negative voltage bias of 50 s, a frequency of 0.001 Hz, a peak-to-valley ratio of 100:1, and at the same time set the reverse current to 1 A / m 2 , and when the reverse current is less than the set value, perform a negative voltage bias for electrode self-cleaning.
[0197] (3) Continuous treatment.
[0198] 4. Treatment effect: The concentration of calcium and magnesium ions is reduced to 112 mg / L, the removal rate is 72%, maintain the cell voltage at 2.3 V, and the power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 4.5 kWh. Example 12
[0199] Continuous method: 1. Treatment object: A 20-ton (20000 L) cooling tower in a thermal power plant, with an initial calcium and magnesium ion concentration (calculated as calcium carbonate) of 200 mg / L.
[0200] 2. Device configuration: Electrode system: The electrolyzed water anode 3 uses a platinum-coated mesh electrode, and the electrolyzed water cathode 2 uses a 316L mesh electrode; Porous insulating filler layer 4: Polypropylene layer (porosity 61%, thickness 0.5 mm, pore diameter 10 - 200 microns).
[0201] The preparation method of the polypropylene layer is as follows: (1) Dissolve 20.0 g of polypropylene particles in 160 mL of decalin at 140 degrees Celsius.
[0202] (2) Add 6.0 g of liquid paraffin.
[0203] (3) Pour the solution into a preheated mold (100 degrees Celsius, depth 0.65 mm).
[0204] (4) Control the cooling rate, cool down from 140 °C to 100 °C at a rate of 0.5 °C per minute, and then cool naturally from 100 °C to 25 °C.
[0205] (5) Demold.
[0206] 3. Operation process: (1) Feeding stage: Pump the water in the cooling tower into the two polar chambers at a flow rate of 1 m / s through a booster pump; (2) Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 1.5 V), set the frequency to a positive voltage bias of 4900 s, a negative voltage bias of 100 s, a frequency of 0.0002 Hz, a peak-to-valley ratio of 100:1, and at the same time set the reverse current to 1 A / m 2 , and when the reverse current is less than the set value, perform a negative voltage bias for electrode self-cleaning.
[0207] (3) Continuous treatment.
[0208] 4. Treatment effect: The concentration of calcium and magnesium ions is reduced to 20 mg / L, and the removal rate is 90%. Maintain the cell voltage at 2.0 V. The power consumption for removing each kilogram of hardness (calculated as calcium carbonate) is 3.4 kWh. Example 13
[0209] Continuous chlorine removal method: 1. Treatment object: 1 ton (1000 L) of circulating water in the data center, with an initial chloride ion concentration of 800 mg / L.
[0210] 2. Device configuration: Electrode system: The electrolyzed water anode 3 uses a ruthenium-iridium-graphene coated mesh electrode, and the electrolyzed water cathode 2 uses a titanium mesh electrode; Porous insulating filler layer 4: Polyamide layer (porosity 52%, thickness 0.8 mm, pore size 10 - 200 microns).
[0211] The preparation method of the polyamide layer is as follows: (1) Dissolve 20.0 g of polyamide (PA) particles in 180 mL of formic acid to form a solution.
[0212] (2) Add 3.6 g of NaCl.
[0213] (3) Pour the solution into a mold (mold depth: 1.0 mm).
[0214] (4) Place it in a fume hood (formic acid volatilization has an irritating odor and corrosiveness), and slowly volatilize the solvent at 35 °C.
[0215] After the solvent has basically evaporated, rinse the surface with water to remove the residual formic acid, and then place it in an oven for vacuum drying at 60 °C.
[0216] (6) Demold after cooling to room temperature.
[0217] 3. Operation process: (1) Feeding stage: Inject the circulating water of the data center into the two electrode chambers at a flow rate of 1 m / s through a booster pump; (2) Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 7.2 V), set the frequency to a positive voltage bias of 95 s, a negative voltage bias of 5 s, a frequency of 0.01 Hz, a peak-to-valley ratio of 50:1, and at the same time set the reverse current to 1 A / m 2 , and when the reverse current is less than the set value, perform a negative voltage bias for electrode self-cleaning.
[0218] (3) Continuous treatment.
[0219] 4. Treatment effect: The chloride ion concentration is reduced to 160 mg / L, and the removal rate is 80%. Maintain the cell voltage at 7.4 V. Example 14
[0220] Chloride removal by continuous method: 1. Treatment object: 5 tons (5000 L) of circulating water from a chemical plant, with an initial chloride ion concentration of 1000 mg / L.
[0221] 2. Device configuration: Electrode system: The electrolyzed water anode 3 uses a ruthenium-iridium coated mesh electrode, and the electrolyzed water cathode 2 uses a titanium-coated ruthenium-iridium mesh electrode; Porous insulating filler layer 4: Polyimide-polypropylene composite layer (porosity 73%, thickness 1 mm, pore diameter 10 - 200 microns).
[0222] The preparation method of the polyimide-polypropylene composite layer is as follows: (1) Add 20.0 g of polyamic acid (PAA) to 180.0 mL of N-methylpyrrolidone (NMP) solvent. In a constant temperature water bath at 25 °C, mechanically stir at a speed of 400 rpm for 6 hours to obtain a homogeneous and transparent PAA / NMP solution with a solid content of 10.0 wt%.
[0223] (2) Add 6.0 g of polypropylene powder (PP) with an average particle size of 20 microns to the above PAA / NMP solution, and disperse it at 25 °C for 30 minutes using a high-speed shear emulsifier (rotation speed 8000 rpm) until there are no visible PP agglomerated particles in the slurry.
[0224] (3) Add 10.0 g of polyethylene glycol 2000 to the slurry and mechanically stir at 500 rpm for 60 minutes at 25 °C to ensure complete dissolution of polyethylene glycol 2000.
[0225] (4) Pour into a mold (mold depth: 2 mm).
[0226] (5) Carry out programmed temperature rise drying and imidization: maintain at 80 °C for 1 h, 120 °C for 1 h, 200 °C for 1 h, 250 °C for 1 h, and 300 °C for 1 h.
[0227] (6) Cool to below 50 °C and demold.
[0228] 3. Operation process: (1) Feeding stage: Inject the circulating water from the chemical plant into the two electrode chambers at a flow rate of 0.5 m / s through a booster pump. (2) Electrochemical treatment: Apply a square wave alternating current (single-stage voltage 5.2 V), set the frequency to a positive pressure bias of 1800 s, a negative pressure bias of 300 s, a frequency of 0.00047 Hz, a peak-to-valley ratio of 20:1, and at the same time set a reverse current of 1 A / m 2 , and perform a negative pressure bias for electrode self-cleaning when the reverse current is less than the set value.
[0229] (3) Continuous treatment.
[0230] 4. Treatment effect: The chloride ion concentration is reduced to 280 mg / L, and the removal rate is 72%. Maintain the cell voltage at 5.3 V. Example 15
[0231] 1. Treatment object: 10 tons (10000 L) of circulating cooling water from a waste power plant, with an initial chloride ion concentration of 1100 mg / L.
[0232] 2. Device configuration: Electrode system: The electrolyzed water anode 3 uses a ruthenium oxide-graphene mesh electrode, and the electrolyzed water cathode 2 uses a platinum-coated graphene mesh electrode; Porous insulating filler layer 4: Polypropylene hollow fiber layer (porosity 68%, thickness 1 mm, pore diameter 0.2 - 0.6 microns).
[0233] The preparation method of the polypropylene hollow fiber layer is as follows (forming a self-supporting layer): (1) Arrange and fix the polypropylene hollow fibers (PPHF) tightly in parallel in the mold frame (mold depth: 2 mm).
[0234] (2) Spray hot melt adhesive at the fiber contact points, and then slightly hot press at 50 °C to bond the fibers.
[0235] (3) After cooling to room temperature, demolding is carried out to obtain a porous layer composed of the pores of PPHF itself.
[0236] 3. Operation process: (1) Feeding stage: Circulating cooling water is injected into the two electrode chambers at a flow rate of 0.5 m / s through a booster pump.
[0237] (2) Electrochemical treatment: Apply a square-wave alternating current (single-stage voltage 4.5 V, frequency 0.00093 Hz (period 1080 s / 18 minutes), peak-to-valley ratio 10:1), and run for 4 cycles (total duration 4320 s).
[0238] (3) Reclaimed water discharge: Open the outlet pipeline 10 of the anode chamber and the outlet pipeline 11 of the cathode chamber, and pump the reclaimed water into the reclaimed water tank 7 at a flow rate of 0.5 m / s.
[0239] (4) Circulating treatment: Repeat 10 times, with a cumulative operation of 40 cycles and a total treatment duration of 43,200 s (12 hours).
[0240] 4. Treatment effect: Raw water tank: All 10,000 L of circulating water from the waste power plant has been treated.
[0241] Effluent water quality: Collect 10,000 L of reclaimed water, the chloride ion concentration drops to 44 mg / L, and the removal rate is 96%.
[0242] Actual energy consumption data: The initial cell voltage is 4.7 V, and the cell voltage rises to 4.8 V (rise value 0.1 V) at the end of the treatment cycle. Example 16
[0243] 1. Treatment object: 5 tons (5000 L) of landfill leachate, with an initial chloride ion concentration of 2800 mg / L.
[0244] 2. Device configuration: Electrode system: The electrolytic water anode 3 uses an iridium oxide-graphene mesh electrode, and the electrolytic water cathode 2 uses an iridium oxide-graphene mesh electrode.
[0245] Porous insulating filler layer 4: Polytetrafluoroethylene composite layer (porosity 56%, thickness 0.5 mm, pore diameter 10 - 500 microns).
[0246] The preparation method of the polytetrafluoroethylene composite layer is as follows: (1) Add 50 mL of deionized water to 100 mL of polytetrafluoroethylene dispersion (solid content 60 wt%, solvent is water), stir well and mix evenly to obtain a diluted polytetrafluoroethylene dispersion with a solid content of 30 wt%.
[0247] (2) Add 45 g of sodium chloride particles with a particle size range of 100 to 150 microns as a pore-forming agent, and continuously stir at a speed of 500 rpm in a constant temperature water bath at 25 °C for 60 minutes to ensure that the pore-forming agent particles are evenly dispersed and there is no agglomeration.
[0248] (3) Pour it into a mold (mold depth: 1 mm).
[0249] (4) Dry at room temperature, and then increase the temperature step by step: dry at 80 °C for 1 hour, remove organic matter at 250 °C for 1 hour, and sinter at 365 °C for 1 hour.
[0250] (5) Cool to below 50 °C and demold.
[0251] 3. Operation process: (1) Feeding stage: Inject concentrated circulating water into the two electrode chambers at a flow rate of 1.0 m / s through a booster pump.
[0252] (2) Electrochemical treatment: Apply a square wave alternating current (single-stage voltage 4.8 V, frequency 0.0017 Hz (period 600 s / 10 minutes), peak-to-valley ratio 10:1), and run for 5 cycles (total duration 3000 s).
[0253] (3) Reclaimed water discharge: Open the outlet pipeline 10 of the anode chamber and the outlet pipeline 11 of the cathode chamber, and pump the reclaimed water into the reclaimed water tank 7 at a flow rate of 1.0 m / s.
[0254] (4) Circulating treatment: Repeat 10 times, with a total of 50 cycles, and the total treatment duration is 30000 s (500 min).
[0255] 4. Treatment effect: Raw water tank: All 5000 L of landfill leachate has been treated.
[0256] Effluent water quality: Collect 5000 L of reclaimed water, the chloride ion concentration drops to 84 mg / L, and the removal rate is 97%.
[0257] Actual energy consumption data: The initial cell voltage is 4.9 V, and the cell voltage rises to 5.0 V (rise value 0.1 V) at the end of the treatment cycle.
[0258] Summarize the above embodiments as shown in Table 1 below.
[0259]
[0260]
Claims
1. A composite electrode unit, characterized in that, It includes: An electrolyzed water cathode (2), a porous insulating filler layer (4), and an electrolyzed water anode (3); the porous insulating filler layer (4) is located between the electrolyzed water cathode (2) and the electrolyzed water anode (3); The internal material of the porous insulating filler layer (4) itself does not contain exchangeable ions, and this internal part refers to the non-surface part; The electrolyzed water cathode (2), the porous insulating filler layer (4), and the electrolyzed water anode (3) are in contact with each other.
2. The composite electrode unit according to claim 1, wherein The porous insulating filler layer (4) as a whole is made of a hydrophobic material; Or the internal material of the porous insulating filler layer (4) itself is a hydrophobic material, and the surface is a hydrophilic material, and this internal part refers to the non-surface part.
3. The composite electrode unit according to claim 1, characterized in that, The porosity of the porous insulating filler layer (4) is 1% - 98%, the thickness is 1 - 5 mm, and the pore diameter is 10 - 500 microns.
4. The composite electrode unit according to claim 1, wherein The material of the porous insulating filler layer (4) is selected from one or a combination of several of the following: polyethylene, polystyrene, polyphenylene sulfide, polyvinyl chloride, polypropylene, polyurethane, polyamide, polyethersulfone, polypropylene hollow fiber, polytetrafluoroethylene, polyvinylidene fluoride, sulfonated polyether ether ketone, polybenzimidazole, polyimide, asbestos, alumina, silicon carbide, silicon nitride, zirconia, boron nitride, mullite, cordierite, aluminum titanate, and silicon dioxide.
5. The composite electrode unit according to claim 3, characterized in that, The surface of the porous insulating filler layer (4) is modified.
6. An electrochemical water treatment system, characterized in that, The system includes: a reaction chamber (5); Inside the reaction chamber (5), there is provided: a composite electrode unit according to any one of claims 1 - 5; Inside the reaction chamber (5), the chamber on the side of the electrolyzed water cathode (2) of the composite electrode unit is the cathode chamber, and the chamber on the side of the electrolyzed water anode (3) of the composite electrode unit is the anode chamber.
7. The electrochemical water treatment system according to claim 6, wherein, The reaction chamber (5) further includes: a power supply (1) for supplying direct current or alternating current to the electrolyzed water cathode (2) and the electrolyzed water anode (3).
8. The electrochemical water treatment system according to claim 6, wherein, The top plate of the reaction chamber (5) is in contact with the top of the composite electrode unit, and the bottom plate of the reaction chamber (5) is in contact with the bottom of the composite electrode unit to achieve physical separation between the cathode chamber and the anode chamber by the composite electrode unit.
9. The electrochemical water treatment system according to claim 6, wherein The system further includes: a raw water tank (6) and a recycled water tank (7); The raw water tank (6) is communicated with the anode chamber through an anode chamber inlet pipeline (8); The raw water tank (6) is communicated with the cathode chamber through a cathode chamber inlet pipeline (9); The recycled water tank (7) is communicated with the anode chamber through an anode chamber outlet pipeline (10); The recycled water tank (7) is communicated with the cathode chamber through a cathode chamber outlet pipeline (11).
10. The electrochemical water treatment system according to claim 9, wherein, The system further includes: a filtering device (12) provided on the cathode chamber outlet pipeline (11) for filtering solid substances in the liquid of the cathode chamber outlet pipeline (11).
11. The electrochemical water treatment system according to claim 9, characterized in that, The raw water tank (6) and the recycled water tank (7) are communicated through a circulation pipeline.
12. An electrochemical water treatment method, characterized in that, The method is carried out using the electrochemical water treatment system according to any one of claims 6 - 11, and the method includes the following steps: Inject raw water containing calcium ions and / or magnesium ions into the cathode chamber and the anode chamber respectively. Turn on the power supply (1), apply direct current or alternating current between the electrolyzed water cathode (2) and the electrolyzed water anode (3), and perform electrolysis to carry out an electrolyzed water reaction in the composite electrode unit; When direct current is provided: Hydrogen is generated in the cathode chamber during electrolyzed water, and an alkaline environment is formed, causing calcium ions and / or magnesium ions to form solid substances and precipitate, reducing the hardness of the water; Oxygen is generated in the anode chamber during electrolyzed water, and an acidic environment is formed; Eventually, alkaline water containing solid substances is obtained in the cathode chamber, and acidic water is obtained in the anode chamber; When alternating current is provided: Before the current direction changes in each alternating current cycle: Hydrogen is generated in the cathode chamber during electrolyzed water, and an alkaline environment is formed, causing calcium ions and / or magnesium ions to form solid substances and precipitate, and part of the solid substances precipitate and crystallize on the surface of the original electrolyzed water cathode (2); Oxygen is generated in the anode chamber during electrolyzed water, and an acidic environment is formed; After the current direction changes in each alternating current cycle: The electrolyzed water cathode (2) and the electrolyzed water anode (3) are inverted, causing the original electrolyzed water anode (3) to become a temporary cathode and start generating hydroxide ions, and the original electrolyzed water cathode (2) to become a temporary anode and start generating hydrogen ions. The hydrogen ions cause the solid substances crystallized on the surface of the original electrolyzed water cathode (2) to dissolve from the surface of the original electrolyzed water cathode (2), achieving in-situ self-cleaning of the electrolyzed water cathode (2); In the next alternating current cycle, in the cathode chamber, calcium ions and / or magnesium ions in the water continuously precipitate and separate out, achieving the purpose of reducing water hardness; Eventually, alkaline water containing solid substances is obtained in the cathode chamber, and acidic water is obtained in the anode chamber.
13. The electrochemical water treatment method according to claim 12, wherein, When the raw water also contains chloride ions, the chloride ions in the anode chamber are oxidized to chlorine gas and removed.
14. The electrochemical water treatment method according to claim 12, characterized in that, When the method is carried out using the electrochemical water treatment system described in claim 9: The raw water tank (6) contains raw water containing calcium ions and / or magnesium ions; The alkaline water and acidic water containing solid substances obtained in claim 12 are discharged into the reclaimed water tank (7) through the cathode chamber outlet pipeline (11) and the anode chamber outlet pipeline (10) respectively and mixed to obtain neutral water.
15. The electrochemical water treatment method according to claim 12, characterized in that, When the method is carried out using the electrochemical water treatment system described in claim 10: The solid substances in the alkaline water containing solid substances are filtered by the filtering device (12).
16. The electrochemical water treatment method according to claim 12, characterized in that, The voltage of the direct current or alternating current is: 1.5V - 30V.
17. The electrochemical water treatment method according to claim 12, characterized in that, When applying the direct current or alternating current, the current density on the electrolyzed water cathode (2) or the electrolyzed water anode (3) is 1 to 1000 A / m 2 .
Citation Information
Patent Citations
Circulating water electrolytic descaling device and descaling method thereof
CN101585569A
Alkaline water electrolysis device
CN116334647A
Electrochemical water scale removal device
CN104291450A
Automatic waste water electrolysis processing apparatus of scale removal
CN206188462U
Water treatment device for removing hardness through fluidization electrolysis
CN220618552U
Cited By
Composite medium, electrochemical reactor and method for treating hardness ions in water
CN121872511A
Composite electrode unit, and electrochemical water treatment system and electrochemical water treatment method
WO2026118567A1